Effects of carnosine and hypothermia combination therapy on hypoxic-ischemic brain injury in neonatal rats - Jun Chul Byun; Seong Ryong Lee; Chun Soo Kim (The Korean Pediatric Society, 2021)
Background Carnosine has antioxidative and neuroprotective properties against hypoxic-ischemic (HI) brain injury. Hypothermia is used as a therapeutic tool for HI encephalopathy in newborn infants with perinatal asphyxia. However, the combined effects of these therapies are unknown. Purpose Here we investigated the effects of combined carnosine and hypothermia therapy on HI brain injury in neonatal rats. Methods Postnatal day 7 (P7) rats were subjected to HI brain injury and randomly assigned to 4 groups: vehicle; carnosine alone; vehicle and hypothermia; and carnosine and hypothermia. Carnosine (250 mg/kg) was intraperitoneally administered at 3 points: immediately following HI injury, 24 hours later, and 48 hours later. Hypothermia was performed by placing the rats in a chamber maintained at 27°C for 3 hours to induce whole-body cooling. Sham-treated rats were also included as a normal control. The rats were euthanized for experiments at P10, P14, and P35. Histological and morphological analyses, in situ zymography, terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assays, and immunofluorescence studies were conducted to investigate the neuroprotective effects of the various interventional treatments. Results Vehicle-treated P10 rats with HI injury showed an increased infarct volume compared to sham-treated rats during the triphenyltetrazolium chloride staining study. Hematoxylin and eosin staining revealed that vehicle-treated P35 rats with HI injury had decreased brain volume in the affected hemisphere. Compared to the vehicle group, carnosine and hypothermia alone did not result in any protective effects against HI brain injury. However, a combination of carnosine and hypothermia effectively reduced the extent of brain damage. The results of in situ zymography, TUNEL assays, and immunofluorescence studies showed that neuroprotective effects were achieved with combination therapy only. Conclusion Carnosine and hypothermia may have synergistic neuroprotective effects against brain damage following HI injury.